Effects of hydrogen on fracture toughness and fracture behaviour of SA508-III steel. (July 2014) - Liu, J. H.; Wang, L.; Liu, Y.; Song, X.; Luo, J.; Yuan, D.
Abstract : Different quantities of H are transported into SA508-III steel by a high pressure thermal charging method. The fracture toughness and fracture behaviour of SA508-III steel with different H contents are investigated by means of three-point bending tests and the J integral method. The results show that the fracture toughness decreases with increasing H content. Based on the analysis of fracture surface, it is clear that with increasing H content, the fracture mechanism changes from normal microvoid coalescence fracture to a mixture of tearing and the dimple model. Because the carbides are strong traps for H, the H is easily transported in the form of Cottrell atmosphere to the carbides following the moving dislocations. Then, H will be enriched at the carbides, and the bonding force between carbides and matrix is decreased in the deforming process. When local H concentration reaches a critical value, microcracks will appear at the interface between the carbides and the matrix, leading to fracture. Moreover, the concentration of H increases continuously at the three-dimensional stress area of the crack tip. The movement and propagation of dislocation will be increased, and the initiation and growth of the crack will be accelerated, which reduces the resistance of crack propagation and decreases the fracture toughness.